The efficacy of combined application of edible coatings and essential oil in mango preservation - Lieu , My Dong; Ha Ngo, Nguyen Nhat; Lieu , Thuy Linh; Nguyen , Kim Thach; Dang , Thi Kim Thuy (Vietnam Journal of Science and Technology, 2018)
The aim of this study was to examine the effect of lemongrass oil (Cympopogon citratus), citronella oil (Cymbopogon winterianus) and cajeput oil (Melaleuca leucadendron) on Aspergillus niger by agar diffusion method. The selected oil was combined with the edible film (chitosan 1% w/v or alginate 1% w/v) and applied to preserve Cat Chu mango (infected by A. niger at105 spore/ml) in 14 days at 30oC. The result showed that essential oils against Aspergillus niger significantly in which lemongrass oil was the most effective inhibitor with a minimum inhibitory concentration (MIC) was 10 μl/mL as compared to MIC of java lemongrass and Melaleuca alternifolia, was 20 μl / mL. The result of the mango preservation showed that, all of the control samples were completely decayed after 10 days of storage while the shelf life of the coated samples was longer than 10 days. The essential oils at high concentrations (10-20 μl / ml) have a negative impact on mango preservation, made fruits bruised on the surface and rapidly decay. The also indicated that, alginate (1% w/v) combines with lemongrass oil (5 μl/mL) maintained the antifungal effect after 14 days of preservation